2002
DOI: 10.3146/pnut.29.2.0003
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolase Activity in Transgenic Peanut

Abstract: Fungal diseases of peanut are responsible for increased production costs and yield losses of up to 50% for peanut producers in the U.S. Few cultivars with disease resistance have been developed through traditional breeding practices. There is an urgent need for developing cultivated peanut (Arachis hypogaea L.) cultivars that are resistant to the broad spectrum of fungal pathogens that pose a recurring threat to peanut health. Hydrolases such as chitinase and β-1-3-glucanase are known to degrade the cell walls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 21 publications
4
40
0
Order By: Relevance
“…Other studies have suggested that additional factors, such as hydrolytic enzymes, are likely to be important in establishing infection and progression of disease caused by S. minor. Based on the observation that coexpression of glucanase and chitinase genes in transgenic tobacco enhanced protection against fungal attack (Zhu et al, 1994), these genes have also been introduced into peanut (Chenault et al, 2002). Expression of multiple resistance genes may offer a better approach for providing greater and longlasting fungal resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that additional factors, such as hydrolytic enzymes, are likely to be important in establishing infection and progression of disease caused by S. minor. Based on the observation that coexpression of glucanase and chitinase genes in transgenic tobacco enhanced protection against fungal attack (Zhu et al, 1994), these genes have also been introduced into peanut (Chenault et al, 2002). Expression of multiple resistance genes may offer a better approach for providing greater and longlasting fungal resistance.…”
Section: Discussionmentioning
confidence: 99%
“…All plant lines positive for the hphgene were also positive for the N gene, indicating an expected 100% co-transformation frequency for the covalently linked genes. The use of hygromycin resistance as a selectable marker in peanut transformation studies has been well established (9,22,24,43). Plant lines E-Nll-3 and ENll-7 which were hygromycin-resistant but PCR-negative were considered putative escapes.…”
Section: Resultsmentioning
confidence: 99%
“…Somatic embryos were initiated using seed from the cultivar Okrun following procedures similar to those previously reported (9,32 …”
Section: Methodsmentioning
confidence: 99%
“…This crop is susceptible to many types of pathogens including those caused by fungi. Chenaulr et al [87] reported the development of transgenic peanuts which were introduced two hydrolase genes, a glucanase from alfalfa (Medicago sativa L.), and a chitinase from rice (Oryza sativa L.) into somatic embryos using biolistic. Although the study focused on seedlings characterization (found up to 37% of hydrolase activity in transgenic lines), these authors assume that transgenic lines obtained could be promising due to high transgene expression what would exhibit some level of resistance to a broad range of fungal pathogens.…”
Section: Peanuts (Arachis Hypogaea)mentioning
confidence: 99%